2019
DOI: 10.5089/9781484396247.001
|View full text |Cite
|
Sign up to set email alerts
|

Debt Build-up in Frontier Low-Income Developing Countries (LIDCs) since 2012: Global or Country-specific Factors and Way Forward?

Abstract: This paper focuses on the debt build-up that frontier low-income developing countries (LIDCs) have faced since 2012. First, it documents a 20-percentage point increase in the external and government debt-to-GDP ratios, a composition shift toward higher nonconcessional debt, and a rise in interest rate payments. Second, using panel regressions, it shows that while both global and country-specific factors are correlated with debt-to-GDP ratios over 1998-2016, global factors dominate for the period 2012-16. Third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Policymakers and practitioners have raised concerns about rising debt levels in emerging and low-income countries since the 2008-09 global financial crisis (Essl et al, 2017;Nishio and Bredenkamp, 2018;Soyres et al, 2019). Cyclical factors such as negative commodity price shocks and loose fiscal policies are typically identified as the main culprits of large surges in government debt.…”
Section: Discussionmentioning
confidence: 99%
“…Policymakers and practitioners have raised concerns about rising debt levels in emerging and low-income countries since the 2008-09 global financial crisis (Essl et al, 2017;Nishio and Bredenkamp, 2018;Soyres et al, 2019). Cyclical factors such as negative commodity price shocks and loose fiscal policies are typically identified as the main culprits of large surges in government debt.…”
Section: Discussionmentioning
confidence: 99%
“…Babu et al (2014), Clements et al, (2003) and Malik et al, (2010) found negative relationship between economic growth and ET ratio. Soyres et al (2019), Kharusi and Ada (2018) and Çiftçioğlu and Sokhanvar (2018) found positive relationships between economic growth and ET ratio in the literature. Zaghdoudi (2018) examined the relationship examined the relationship between human development index and ET for a panel of 95 developing countries for the period 2002 and 2015.…”
Section: Introductionmentioning
confidence: 94%
“…Only a few studies empirically assess the characteristics and drivers of capital flows to FMEs (de Soyares et al 2019;Silva et al 2021). Silva et al (2021: 10) stress that the increase in bond issuance by EMEs after the GFC coincided with a decreasing trend in global financial market volatility, suggesting that during calm periods in global financial markets, foreign investors have a higher appetite for risk and, consequently, are more willing to invest in higher yield, but also speculative grade and higher risk securities, such as FMEs' bonds.…”
Section: The Dynamics Of Financial Globalisation and The Emergence Of...mentioning
confidence: 99%